Get the answers you need at Westonci.ca, where our expert community is dedicated to providing you with accurate information. Discover precise answers to your questions from a wide range of experts on our user-friendly Q&A platform. Get quick and reliable solutions to your questions from a community of experienced experts on our platform.
Sagot :
(one way is to subsitute since both equal 9 you do 3x-4y=-3x+2y then add 3x to both sides 6x-4y=2y add 4y to both sides 6x=6y divide by 6 x=y now subsitute 3x-4x=9 -x=9 multiply -1 x=9 x=y y=-9)
use elimination
add them together to cancel x terms
3x-4y=9
-3x+2y=9 +
0x-2y=18
-2y=18
divide by 2
-y=9
multiply -1
y=-9
subsituete
3x-4y=9
3x-(4 times -9)=9
3x-(-36)=9
3x+36=9
subtract 36 from both sides
3x=-27
divide both sides by 3
x=-9
x=-9
y=-9
the answer is in (x,y) form
(-9,-9)
the answer is none of them (D is closest)
use elimination
add them together to cancel x terms
3x-4y=9
-3x+2y=9 +
0x-2y=18
-2y=18
divide by 2
-y=9
multiply -1
y=-9
subsituete
3x-4y=9
3x-(4 times -9)=9
3x-(-36)=9
3x+36=9
subtract 36 from both sides
3x=-27
divide both sides by 3
x=-9
x=-9
y=-9
the answer is in (x,y) form
(-9,-9)
the answer is none of them (D is closest)
Answer:
(-9,-9)
Explanation:
The two given equations are:
3x - 4y = 9
-3x + 2y = 9
First step is to add the two equations in order to eliminate the x.
This will give us:
-4y + 2y = 9 + 9
-2y = 18
y = -9
Now, we substitute with the value of y in any of the equations to get x as follows:
3x - 4y = 9
3x - 4(-9) = 9
3x + 36 = 9
3x = -27
x = -9
Hope this helps :)
Thank you for your visit. We're dedicated to helping you find the information you need, whenever you need it. We hope our answers were useful. Return anytime for more information and answers to any other questions you have. Thank you for trusting Westonci.ca. Don't forget to revisit us for more accurate and insightful answers.